PENERAPAN METODE EKSPERIMEN PADA PEMBELAJARAN FISIKA SISWA KELAS X SMAN 3 LUBUKLINGGAU TAHUN PELAJARAN 2018/2019 - Zakiya Z.; Ahmad Amin; Endang Lovisia (SILAMPARI JURNAL PENDIDIKAN ILMU FISIKA, 2019)
This research titled "Application of Experimental Methods in Physics Learning Class X of Lubuklinggau 3 State Senior High School 2018/2019 Academic Year " The purpose of this study was to determine the completeness of Physics Learning Outcomes of Grade X Students of SMAN 3 Lubuklinggau Academic Year 2018/2019. This type of research is a quasi-experiment carried out without a comparison group or class. The population in this study were all students of class X IPA 3 Lubuklinggau High School, which amounted to 144 students and as a sample of the experimental class were 36 students in class X Science as many as 36 students. sampling in this study was conducted randomly (simple random sampling) by drawing. Data collection is done by written test technique. Student test score data were analyzed using the t-test. Based on the results of hypothesis testing with a significant level of α = 0.05 obtained t_count> t_table = (8.76> 2.00) which means H_0 is rejected and H_a is accepted. So that it can be concluded that the physics learning outcomes of class X IPA 2 students of SMA 3 Lubuklinggau in the 2018/2019 Academic Year after applying the experimental method were significantly completed.